Phytogenic feed additives mixture enhances the lactational performance, feed utilization and ruminal fermentation of Friesian cows. Issue 6 (1st December 2021) - Kholif, A. E.; Hassan, A. A.; El Ashry, Ghada M.; Bakr, M. H.; El-Zaiat, H. M.; Olafadehan, O. A.; Matloup, O. H.; Sallam, S. M. A.
Abstract: The assay aimed to evaluate the effect of feeding a recently developed phytogenic feed additives mixture in diets of lactating Friesian cows ( n = 30; 514 ± 10.1 kg body weight) for 3 months. Cows were stratified into three groups of 10 cows each and fed a control diet alone or the control diet supplemented with the additives mixture at 3 g (PHY3) or 6 g (PHY6)/cow daily. Menthol, levomenthol, β-linaloolm, anethole, hexadecanoic acid and p -menthane were the principle compounds identified in the additives mixture. The PHY3 increased ( p < 0.01) intake and nutrient digestibility. PHY3 and PHY6 increased ( p < 0.01) ruminal pH, total volatile fatty acids, propionate and acetate. PHY3 and PHY6 improved serum total protein and antioxidant capacity and decreased the concentrations of serum urea-N, triglycerides, total lipids, cholesterol and malondialdehyde ( p < 0.05). PHY3 increased milk production and milk content of total solids, protein, lactose and fat. Both PHY3 and PHY6 did not affect mineral concentrations in blood or milk. It is concluded that the inclusion of 3 g/cow/d of feed additives mixture in the lactating Friesian cows diet enhanced milk production and feed utilization, with negative effects observed with increasing the dose of additives mixture to 6 g/cow daily.